Engineering and design : design, in situ thermal remediation (EM (Series) (United States. Army. Corps of Engineers) ;, 2009)
This manual provides guidance and background for the appropriate screening and selection of in situ thermal remediation (ISTR) technologies and is intended for use by engineers, geologists, hydrogeologists, soil scientists, chemists, project managers, and others who possess a technical education but only the broadest familiarity with ISTR technologies.